Seguimiento A La Gestion De Cobranza De La ¨Empresa Marcimex¨ Sucursal Babahoyo - Icaza Flores, Katherine Belen (2018)
Currently the productive companies that are dedicated to the purchase and sale of goods or services offer, in cash and on credit, the acquisitions made, the businesses choose to implement this method in order to increase operations and make the relationship with customers and the market in general more efficient that cash sales and credit sales are the main source of income in a deal. Sales made to credits constitute an important tool for The growth of business in different markets is chosen by this method with the purpose of increasing operations and making more efficient the relationship with customers and the market in general. This treaty will be developed in the Marcimex Agency S.A - Babahoyo, this warehouse belongs to the Commercial Sector dedicated to the wholesale and retail of consumer appliances and solutions for the home, is the third company National with the highest capital within this specific sector. The company starts its activities in the city of Babahoyo in August of the year of 2007 staying in been active until today. The objective of this study is to focus on follow-ups to the processes of the credit and collections manual. At the time of granting credits, aroused facts that are not favorable, which therefore affects the liquidity of the company as when these credits are not canceled within the established deadlines and a act immediately since these accounts do not do the respective follow-up they become uncollectible accounts is where the collection management intercedes